The Effect of S.A.Q and ( MetCon) Training to Developing Some Motor Abilities, Explosive Ability and Defensive Foot Movements for Young Basketball Players - Ahmed Ishhab Abdulhussein; Jamal Sabri Faraj Al Abdullha (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research aims to prepare (S.A.Q) and (MetCon) exercises to develop some motor abilities, explosiveability and defensive foot movements for young basketball players, and to learn about the effect of (S.A.Q)training and (MetCon) in the development of some movement abilities, explosive ability and defensivefoot movements of young basketball players. The researcher hypothesized that there is a positive effect of(S.A.Q) training, which consists in developing some movement abilities, explosive ability and defensivefoot movements for young basketball players. The researcher used the experimental method using themethod of (the two equal experimental groups) of pre and post-test due to its suitability to the nature ofthe research, the research sample was represented by (12) players who were deliberately selected from theresearch community and randomly assigned to two groups, two experiments, a group of (S.A.Q) exercisesand a group of MetCon exercises. The most important conclusion is that (S.A.Q) training has a positiveeffect in developing some movement abilities, explosive ability and defensive foot movements for youngbasketball players. Through the conclusions, he mentioned some recommendations, the most important ofwhich is the emphasis on the use of (S.A.Q) and (MetCon) training to develop the defensive foot movementsof young basketball players. And the use of complex exercises by integrating motor abilities and explosiveability with defensive foot movements in similar conditions according to the motor path of the skill.